2012
DOI: 10.1007/s00520-012-1644-z
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of agents for the management of gastrointestinal mucositis in cancer patients

Abstract: Purpose The aim of this study was to review the available literature and define clinical practice guidelines for the use of agents for the prevention and treatment of gastrointestinal mucositis. Methods A systematic review was conducted by the Mucositis Study Group of the Multinational Association of Supportive Care in Cancer/International Society of Oral Oncology (MASCC/ISOO). The body of evidence for each intervention, in each cancer treatment setting, was assigned an evidence level. Based on the evidence le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 180 publications
(107 citation statements)
references
References 135 publications
1
96
0
10
Order By: Relevance
“…A possible explanation for these observations requiring additional investigation is that clinical manifestations of diarrhoea are not exclusively the result of mucositis and that, as in the non-oncology population, disruptions in the normal microbial flora may result in disturbed bowel function. Data supporting such a hypothesis have been derived from intervention studies using probiotic factors, which have proven effective in reducing cancer therapy-induced diarrhoea in the preclinical and clinical settings [75,76]. An additional factor affecting the role of the microbiota may be the effect of the tumour on the immune response.…”
Section: Gut Microbiomementioning
confidence: 99%
“…A possible explanation for these observations requiring additional investigation is that clinical manifestations of diarrhoea are not exclusively the result of mucositis and that, as in the non-oncology population, disruptions in the normal microbial flora may result in disturbed bowel function. Data supporting such a hypothesis have been derived from intervention studies using probiotic factors, which have proven effective in reducing cancer therapy-induced diarrhoea in the preclinical and clinical settings [75,76]. An additional factor affecting the role of the microbiota may be the effect of the tumour on the immune response.…”
Section: Gut Microbiomementioning
confidence: 99%
“…The severity of gastrointestinal adverse effects associated with 5FU/LV chemotherapy is increased with the incorporation of oxaliplatin in the regimen (Bano and Najam, 2013b;Bano et al, 2013c) FOLFOX4 is associated with grade 3 or 4 diarrhea (Uncu et al, 2013) and nausea/vomiting (Lee et al, 2013) protocol. Diarrhea is a frequent dose limiting toxicity of FOLFOX (Comeau and Mohundro, 2013) Lactobacillus spp containing probiotic treatment is recommended in chemotherapy or radiotherapy induced diarrhea (Gibson et al, 2013). Nausea and vomiting can be effectively managed by dexamethasone and indisetron in optimal doses in approximately 80% cases (Nakatsumi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic gastrointestinal side effects occur in over 30% of patients [42]. A meta-analysis concluded that probiotic treatment with Lactobacillus spp could prevent chemotherapy and radiation enteritis-induced diarrhea in patients with pelvic malignancies [52].…”
Section: Radiation Enteritismentioning
confidence: 99%